2019
DOI: 10.1016/j.jtrangeo.2019.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Developing a low-cost airline in a semi-protected regime: Comparing China to Europe and the US

Abstract: The US and Europe have long experienced the expansion of low-cost carriers (LCCs) in the aftermath of extensive aviation liberalisation offering free access to the market for US and European airlines, respectively. More recently, following the opening of the progressive aviation market, China has also emerged as a country that welcomed LCCs to some extent, but has not subscribed to full liberalisation. In this context, our paper compares China's largest LCC, Spring Airlines, to the largest European (Ryanair an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
1
13
1
Order By: Relevance
“…This clearly shows that Spring, Lucky and China United deliberately devoted a significant amount of their capacity on the routes that are not served by other airlines. This pattern is similar to that of the major US and European LCCs reported in Dobruszkes and Wang (2019). In contrast, Jiuyuan and West Air's monopoly routes only accounted for 12% and 15% of their total routes, respectively.…”
Section: Market Structure Of Lcc Routessupporting
confidence: 83%
See 3 more Smart Citations
“…This clearly shows that Spring, Lucky and China United deliberately devoted a significant amount of their capacity on the routes that are not served by other airlines. This pattern is similar to that of the major US and European LCCs reported in Dobruszkes and Wang (2019). In contrast, Jiuyuan and West Air's monopoly routes only accounted for 12% and 15% of their total routes, respectively.…”
Section: Market Structure Of Lcc Routessupporting
confidence: 83%
“…It is also the only commercial airline approved by Air Force to use Beijing Nanyuan Airport (a military air base with civil aviation facilities) as its home airport. Dobruszkes and Wang (2019). In addition, all the degree distributions in Figure 5 clearly follow a power law.…”
Section: China United Airlinesmentioning
confidence: 78%
See 2 more Smart Citations
“…For instance, the authors found that a lack of secondary, low cost airports affected the performance of the LCCs in Asia. Dobruszkes and Wang (2019) assessed the scope for LCCs in not fully deregulated regimes. They found that low cost carriers like Spring Airlines in China lack free access to the market as trunk routes are still protected to some extent in favor of the large FSNCs.…”
Section: Low Cost Carriers: Business Model Geographical Coverage Andmentioning
confidence: 99%